1974
DOI: 10.1677/joe.0.0630451
|View full text |Cite
|
Sign up to set email alerts
|

Parturition in the Cow: Endocrine Changes in Animals With Chronically Implanted Catheters in the Foetal and Maternal Circulations

Abstract: Intravascular catheters were placed in the umbilical, uterine and maternal peripheral circulations of 16 Jersey cows between 240 and 260 days of gestation. Foetal plasma cortisol, blood gases and pH, and maternal plasma oestrogen, progesterone and cortisol were measured in ten animals during late pregnancy and throughout spontaneous parturition; all delivered live foetuses although parturition was earlier than normal and the placenta was generally retained. The gradual pre-partum rise in foetal plasma cortisol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
57
3

Year Published

1977
1977
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(72 citation statements)
references
References 22 publications
10
57
3
Order By: Relevance
“…Blood gas values and pH in samples taken from the umbilical cord (Schuijt 1992) or the dorsal digital vein of a front leg (Szenci et al 1988) during calving confirmed earlier data from experiments with chronically catheterized foetal calves (Comline et al 1974) that no significant changes take place in the oxygenation and acid base balance during the most part of an uncomplicated birth process. It is only during the last hour before expulsion that a more sustained hypoxia and acidosis develops, most probably as the result of a more permanent reduction in uterine blood flow.…”
Section: The Calf During and Immediately After Birthsupporting
confidence: 72%
“…Blood gas values and pH in samples taken from the umbilical cord (Schuijt 1992) or the dorsal digital vein of a front leg (Szenci et al 1988) during calving confirmed earlier data from experiments with chronically catheterized foetal calves (Comline et al 1974) that no significant changes take place in the oxygenation and acid base balance during the most part of an uncomplicated birth process. It is only during the last hour before expulsion that a more sustained hypoxia and acidosis develops, most probably as the result of a more permanent reduction in uterine blood flow.…”
Section: The Calf During and Immediately After Birthsupporting
confidence: 72%
“…A high incidence of gestational loss in early to mid-pregnancy is the most remarkable feature of the cloning of cattle [1], but problems in the peripartum period, such as delayed parturition, large offspring syndrome (LOS) and neonatal death, are also factors in decreasing the production efficiency [1][2][3][4]. LOS and poor sign of parturition in pregnant cows cause dystocia leading to losses of dams and newborn calves.Cortisol, a glucocorticoid secreted from the fetal adrenal cortex, plays an important role in the initiation and progression of parturition [5,6]. The secretion of cortisol from the fetal adrenal cortex is facilitated particularly during the last week of gestation and reaches a peak just before parturition [5].…”
mentioning
confidence: 99%
“…The secretion of cortisol from the fetal adrenal cortex is facilitated particularly during the last week of gestation and reaches a peak just before parturition [5]. In the placenta, cortisol promotes the synthesis of estrogens that induce relaxation and dilation of the birth canal [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because this coincides with an increase in circulating oestrogens, it was suggested that pregnenolone, the common precursor substrate for the synthesis of both steroids, is diverted from progesterone to oestrogen synthesis (Schuler et al, 1994). The more abrupt decrease in circulating progesterone 2-3 days prior to parturition is interpreted as being due to luteolysis and increased progesterone metabolism, likely precipitated by the increase in foetal cortisol production and release, a crucial component of the foetal endocrine signals that initiate parturition (Comline et al, 1974;Fairclough et al, 1975;Hunter et al, 1977).…”
Section: Progesterone Productionmentioning
confidence: 99%